On the long-term macroeconomic effects of social security spending: evidence for 12 EU countries - Pereira, Alfredo M.; Andraz, Jorge M. (Evora, 2014)
"We estimate the long-term impact of social security and social protection spending in a set of twelve EU countries. We estimate country-specific VARs relating GDP, unemployment, savings, and social spending. We find that social spending has a negative effect in most countries while the effects on savings are either not significant or positive but small. In turn, the negative effects on output are significant and in some cases large. Unemployment is the dominant channel through which social spending affects output. Our results imply that any increase in generosity would, under the current situation, bring detrimental macroeconomic effects. In addition, a less distortionary tax mix should be used to finance redistributive spending and the insurance component of the systems should be changed in the direction of a capitalization regime based on defined contributions. Obviously, this transition would take time and would not be costless but neither is maintaining the status quo."